Skin-Infiltrating CD8+ T Cells Initiate Atopic Dermatitis Lesions - Anà Hennino; Marc Vocanson; Y. Toussaint; Karen Rodet; Josette Bénetière; Anne-Marie Schmitt; Marie-Françoise Ariès; F. Bérard; Aurore Rozières; Jean‐François Nicolas (2007)
Skin lesions in the allergic form of atopic dermatitis (AD) are induced by allergen-specific T cells that infiltrate the skin at the site of allergen exposure. Although Th2-type CD4+ T cells appear to be crucial in AD pathophysiology, little is known about the contribution of CD8+ T cells in the development of the allergic skin inflammation. In the present study, we have analyzed the respective role of CD8+ and CD4+ T cells in the development of AD skin lesions in a mouse model of allergen-induced AD. In sensitized mice, CD8+ T cells are rapidly and transiently recruited to the allergen-exposed site and initiate the inflammatory process leading to skin infiltration with eosinophils and Th1/Th2-producing cells. CD8+ T cell-depleted mice show no inflammation, demonstrating that these cells are mandatory for the development of AD. In contrast, CD4+ T cell-depleted mice develop a severe form of eczema. Furthermore, adoptive transfer of CD8+ T cells from sensitized mice into naive recipient mice leads to skin inflammation soon after allergen exposure. These data indicate that allergen-primed CD8+ T cells are required for the development of AD-like lesions in mice.